Content analysis of thinking skills level in reading questions of tenth grade of EFL textbook in Indonesia - Muhsinin, Muhsinin; Sahni, Sahni; Ariawan, Soni; Hamdi, M. Zulpiani (UPT Bahasa Universitas Tanjungpura, 2025)
Textbooks play a pivotal role in education, serving as primary learning resources and guiding both teaching and learning activities. Despite their importance, limited research has examined the cognitive levels of reading comprehension questions in EFL textbooks. This study aimed to analyze the level and distribution of thinking skills reflected in the reading questions of the tenth-grade Indonesian EFL textbook Bahasa Inggris. Utilizing content analysis, the study employed coding tables and checklists based on the revised Bloom